Compact Substrate Integrated Waveguide (SIW) Based Four-Element MIMO Antenna for 5G NR Applications - Pramono, Subuh; Sulistyo, Meiyanto Eko; Ibrahim, Muhammad Hamka; Rahutomo, Faisal; Sutrisno; Hariyono, Joko (2024 7th International Conference of Computer and Informatics Engineering (IC2IE), 2024)
A compact SIW-based four-element MIMO antenna is proposed for 5G NR applications operating 26.5 - 29.5 GHz. SIW antennas function on the same principle as waveguides but are incorporated onto a substrate. Because of their high-power handling capacity and low loss, SIW antennas are well-known for serving high-frequency applications. MIMO antenna uses SIW-based four-element antennas. The proposed SIW based four-element MIMO antenna has a compact size of 36.8 x 36.8 x 0.578 mm 3 . It has an ultra-wideband impedance bandwidth of 10.32 GHz, which spans from 24.68 to 35 GHz. The H and E planes are used to figure out the radiation patterns of the proposed antenna, the main lobe direction of the antenna is 3° in the E-plane, and its half power beam width (HPBW) is 49°. The H-plane achieves an HPBW of approximately 71°. The maximum gain can be obtained at around 7.21 dBi. The obtained ECC level is less than 0.02, and the DG values are higher than 9.95 along the frequency spectrum for 5G NR applications.